Baquero De la Calle, J. (2007). El Derecho... ¿para qué? Quito: CEP - Rodrigo Merino Barros (Universidad Hemisferios, 2008)
This paper provides an overview of the work “El Derecho... ¿para qué?” of Jaime Baquero de la Calle. The overview analyzes the sources, the type of documents and examples that are used in it. Includes an explanation of the structure of the document, emphasizing the utility that provides this publication for students of law.